Comparing scanpaths during scene encoding and recognition: A multi-dimensional approach - Tom Foulsham; Richard Dewhurst; Marcus Nyström; Halszka Jarodzka; Roger Johansson; Geoffrey Underwood; Kenneth Holmqvist (Bern Open Publishing, 2012)
Complex stimuli and tasks elicit particular eye movement sequences. Previous research has focused on comparing between these scanpaths, particularly in memory and imagery research where it has been proposed that observers reproduce their eye movements when recognizing or imagining a stimulus. However, it is not clear whether scanpath similarity is related to memory performance and which particular aspects of the eye movements recur. We therefore compared eye movements in a picture memory task, using a recently proposed comparison method, MultiMatch, which quantifies scanpath similarity across multiple dimensions including shape and fixation duration. Scanpaths were more similar when the same participant's eye movements were compared from two viewings of the same image than between different images or different participants viewing the same image. In addition, fixation durations were similar within a participant and this similarity was associated with memory performance.